Analisis Fluktuasi Harga pada Transaksi Jual Beli Perhiasan Emas Dalam Perspektif Etika Bisnis Islam - Diyas Yuri Pristinta; Yuliani (Indonesian Journal of Islamic Economics and Business, 2022)
The stable price of gold makes this precious metal much sought after by buyers for the purpose of investment or jewelry and collections. So far, businesses at kiosks that provide gold as a commodity have never been abandoned by buying and selling activities, be it marketing at gold kiosks or marketing by customers to be replaced and buyers' requests for cash. The issue raised in this research is how to apply the accumulation and decline in value in the gold jewelery trade from the ethical perspective of the Islamic business sector. This research uses qualitative methods and uses bibliography research. The source of information used in this research is an inferior data source because this research is a bibliography research. This research uses the method of collecting bibliography information and using content analysis technology to explore the content or meaning of documents, literary creations, articles, and others in the form of irregular information. The results of this research are that there are still many situations that do not match the ethics of the Islamic business sector in the practice of increasing and decreasing the value of gold jewelry prices in the lives of today's citizens. Because consumers and traders almost do not have negotiations in practice, so that in this business the consumer cannot fulfill the right to get the price that is in the business of buying and selling gold jewelry. At the same time, from the ethical perspective of the Islamic trade sector, the accumulation and reduction of gold trading prices must be in accordance with the ethical principles of the Islamic business sector, including monotheism, balancing or equality, free will, responsibility and honesty and truth.